2005
DOI: 10.1097/00004872-200501000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II accelerates endothelial progenitor cell senescence through induction of oxidative stress

Abstract: Ang II increases gp91phox expression in EPC, which may contribute to oxidative stress, as evidenced by peroxynitrite formation. Ang II accelerates the onset of EPC senescence via increased oxidative stress, which may be related to telomerase inactivation. In addition, Ang II-induced EPC senescence leads to the impairment of proliferative activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
183
3
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(193 citation statements)
references
References 30 publications
4
183
3
3
Order By: Relevance
“…Chronic activity of Nox enzymes also inactivates telomerase and may promote senescence of endothelial progenitor cells [90]. Therefore, inhibition of Nox2 and/or Nox1 is likely to be useful for the prevention and treatment of atherosclerosis.…”
Section: Nox Enzymes and Atherosclerosismentioning
confidence: 99%
“…Chronic activity of Nox enzymes also inactivates telomerase and may promote senescence of endothelial progenitor cells [90]. Therefore, inhibition of Nox2 and/or Nox1 is likely to be useful for the prevention and treatment of atherosclerosis.…”
Section: Nox Enzymes and Atherosclerosismentioning
confidence: 99%
“…Decreased numbers and increased proportion of senescent EPC has been reported in patients with preeclampsia (34) or hypertension (35). Angiotensin II can induce EPC senescence through the induction of oxidative stress and influence telomerase activity (36). Oxidized low-density lipoprotein induces EPC senescence and dysfunction (37).…”
Section: Senescence Of Endothelial Progenitor Cells (Epc)mentioning
confidence: 99%
“…In fact, the level of EPCs has been reported to be predictive of CV events, 4 and the loss of EPCs to have a role in the development of CV disease. Imanishi et al 5 have reported that Angiotensin II (Ang II) accelerates the onset of EPCs senescence through enhanced oxidative stress, which in turn leads to the impairment of proliferative activity in EPCs. In addition, the correction of EPCs dysfunction by treatment with Ang II type 1 receptor blockers further points to a role for Ang II and Ang II-mediated oxidative stress in EPC 6,7 as well as endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%